Prevalence of viral hepatitis type C in blood donors in Peru 2016 - 2017 - Bellido, Alvaro (2021)
Objectives: Knowing the current prevalence of hepatitis C virus infection has taken great importance nowdays due to the new advances in the treatment of hepatitis C virus infection in which the new direct-acting antivirals have demonstrated a high rate of sustained viral response. Materials and methods: This is a descriptive study based on the detection of anti VHC in the blood banks of “Ministerio de Salud del Perú” according to the information obtained from “Programa Nacional de Hemoterapia y Bancos de Sangre” (PRONAHEBAS). Results: In our study, the prevalence of anti-hepatitis C antibodies in blood donors nationwide was 0.428% in 2016 and 0.301% in 2017. Conclusion: To know updated data about the prevalence of hepatitis C virus infection in our population. It is isease and drastically reduce the infection rate according to the WHO target for 2030.